G630 Parents' experience of managing their child's post-tonsillectomy pain at home: An exploratory qualitative study. (27th April 2016) - Longard, J; Chorney, J; Hong, P; Williams, A; Twycross, A
Abstract : Background: Despite well-established evidence to guide pain management many children experience moderate to severe pain at home after common paediatric surgeries (Kankkunen et al ., 2009; Shum et al ., 2012; Wiggins, 2009). Due to changes in children's healthcare services, including shorter hospital stays, the task of managing children's postoperative pain is often transferred to parents. Aim: To understand parents' experiences of managing their child's post-tonsillectomy pain at home, including barriers and facilitators to optimal pain management. Methods: Semi-structured interviews was carried out from December 2013–February 2015 with 10 parents of typically-developing children, aged 5–6 years, who had a tonsillectomy with or without adenoidectomy, and experienced no complications leading to hospitalisation. Interviews were conducted with parents within three months of their child's surgery. Interviews were transcribed verbatim and content analysis was used to identify themes in parents' experiences. Results: All children reportedly experienced some postoperative pain although for some children this was only mild. Parents used analgesic drugs and non-drug methods to manage their child's pain. Parents reported that their child's recovery at home placed significant short-term burdens on their family, but many felt the process was worthwhile given the potential long-term health benefits for their child. Parents reported that they were generally satisfied with the information they received but some recommendations for further information were provided. Discussion: The results of this study provide an indication of the barriers and facilitators for parents managing their child's pain at home. This provides an opportunity to reflect on practices and to identify additional strategies that can be used to support parents in this context. Conclusions: This study provides a first-hand account of parents' experiences of managing their child's postoperative pain at home and reveals some of the factors that help and hinder parents' management of their child's pain.